Peran Mahasiswa Dalam Meningkatkan Kemampuan Komunikasi Interpersonal (Publik Speaking) Di Smp Negeri 4 Fillial Kelas Jauh Usaha Jaya - Rustam, Nurul Khairunnisa; Sumarsi; Abdullah; Iin Kahina, Dwi (LPPM IAIN Sorong, 2024)
The ability to communicate is very important to instill in students. In this research, we looked at the interpersonal communication (public speaking) skills of students at SMP Negeri 4 Fillial, Usaha Jaya Distance Class. The method used in this research is a qualitative research method by collecting data by observation. The results of this research show that students' ability to communicate is very low, so efforts are made to improve their abilities through training, such as training to improve self-confidence, intonation and articulation, as well as training facial expressions when speaking. It is hoped that this research will be able to contribute to the level of education in Indonesia